Menschliche Bandwurmfunde aus Gottwaldov - Rehka, V (Angewandte Parasitologie, 1981)
The author deals with the problems of taeniidoses in the region of Gottwaldov and informs about findings of taeniidoses in the parasitological laboratory at OHS Gottwaldov from 1956-1978. During this period of time 31,502 patients were examined because of enteroparasites, and taeniarhynchosis was determined in 355 cases (1.1%). Taenia sodium was only shown in 2 cases. Hymenolepis nana was shown with 18 patients (0.06%). Furthermore 3 cases of echinococcoses in human beings are described, once in the heart, twice in the lungs. In the text there is also a reference to the experiences in treatment. The author points out that taeniidoses have been registered (Surveillance method) in Czechoslovakia since 1979.
Keywords: hymenolepiáza; kardiomyopatie; Radiography; Sputum; Czechoslovakia; tenióza; lidé středního věku; předškolní dítě; lidé; Cestode Infections; Adult; Cardiomyopathies; Middle Aged; Hymenolepiasis; dospělí; echinokokóza; sputum; Female; echinokokóza plic; Echinococcosis, Pulmonary; Československo; Male; ženské pohlaví; feces; Humans; mužské pohlaví; Taeniasis; Feces; cestodózy; Echinococcosis; Child, Preschool; radiografie